Mutualism Partnership: Sebuah Pola Kemitraan Pengolahan Limbah Medis Kota Jakarta Timur - Anisa Pramitasari; Grace Sharon; Efendy Yusuf (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2023)
The emergence of Covid-19 some time ago had an impact on increasing the volume of B3 medical waste. The Ministry of Environment and Forestry (KLHK) noted an increase in B3 medical waste ranging from 30% to 50%. In the household environment, B3 waste has increased significantly from 1,538.77 tons in 2020 to 2,106.651 tons in 2021. Medical mask waste is the most dominant. Currently 2.8 million medical mask waste is produced every one minute. Medical mask waste is included in hazardous waste. B3 waste management based on Government Regulation No. 101 of 2014 that medical waste requires special treatment and facilities from the time the waste is produced to its destruction (from candle to grave). The partnership practice is an alternative chosen by the City Government of East Jakarta in managing B3 waste. The results of the research identification lead to a pattern of mutualism partnership. Partnership is considered as a strategy but its implementation tends to be